War and oncology: cancer care in five Iraqi provinces impacted by the ISIL conflict - Skelton, Mac; Al-Mash'hadani, Ahmed Khalid; Abdul-Sater, Zahi; Saleem, Mohammed; Alsaad, Saad; Kahtan, Marwa; Al-Samarai, Ahmed Hazim; Al-Bakir, Ahmed Moyed; Mula-Hussain, Layth (Frontiers in Oncology, 2023)
Iraq’s healthcare system and oncology infrastructure have endured war, sanctions, and instability over three decades. Most recently, the Islamic State of Iraq and the Levant (ISIL) violently occupied large portions of the country’s central and northern provinces between 2014 and 2017, causing devastating impacts on public cancer centers across central and northern Iraq. Focusing on the five Iraqi provinces previously under full or partial ISIL occupation, this article examines the immediate and long-term impacts of war on cancer care across three periods (before, during, and after the ISIL conflict). As there is little published data on oncology in these local contexts, the paper relies primarily upon the qualitative interviews and lived experience of oncologists serving in the five provinces studied. A political economy lens is applied to interpret the results, particularly the data related to progress in oncology reconstruction. Conflict generates immediate and long-term shifts in political and economic conditions that, in turn, shape the rebuilding of oncology infrastructure. The documentation of the destruction and reconstruction of local oncology systems is intended to benefit the next generation of cancer care practitioners in Iraq and the broader Middle East region in their efforts to adapt to conflict and rebuild from the legacies of war.